On an empty stomach : two hundred years of hunger relief - Scott-Smith, Tom, 1980- (Cornell University Press, 2020)
"This book examines the practical techniques humanitarians have used to manage and measure starvation, from Victorian soup kitchens to space-age, high-protein foods. Tracing the evolution of these techniques since the start of the nineteenth century, the book argues that humanitarianism is not a simple story of progress and improvement, but is profoundly shaped by sociopolitical conditions"--